Cherubim: Fine Needle Aspiration Cytology Findings - Khalid, Abdul; Haque, Anwar Ul; Baqai, Tariq (International Journal of Pathology, 2018)
Abstract: A 52 years old lady presented with history of weakness and breathlessness on exertion. She noticedchanges in her facial appearance around twenty years of age which continued to advance progressively over thelast three decades. On physical examination her face showed advanced deformity and asymmetry in both horizontaland vertical planes. There was significant deformity of maxilla with prominent and unequal enlargement of malareminences, stretched overlying skin and prominent superficial veins. The Fine Needle Aspiration Cytology fromprominent right maxillary area was consistent with the diagnosis of cherubism